Maternal perception, barriers, and facilitators regarding oral rehydration salt solution in diarrhoeal disease: A qualitative study in Bangladesh - Md Ridwan Islam; Md Fuad Al Fidah; Sneha Paul; Mahfuz-Un Nesa; Sarashwati Giri; Syed Jayedul Bashar; Chowdhury Ali Kawser; Tahmeed Ahmed; Sharika Nuzhat (PLoS ONE, 2025)
Background Although oral rehydration salt (ORS) solution is a lifesaving management for diarrhoea, its exertion is still surprisingly low among caregivers. As mothers are considered to be the primary caregivers, they bear the responsibility of administering medications to their children. We aimed to evaluate maternal perceptions along with the barriers and facilitators in play that are affecting ORS administration among children in Bangladesh. Methods The study was conducted at Dhaka Hospital of the International Centre for Diarrhoeal Diseases Research, Bangladesh through a qualitative approach. In-depth Interviews (IDIs) were conducted on thirty-one mothers of under-5 children reporting to the hospital from February to April 2024. Qualitative content analysis method was used to describe and analyse the transcribed data. Findings The mothers held several misconceptions regarding the administration of ORS. Majority of the participants thought their child could receive ORS through their breastmilk, which was an interesting finding. Along with this, mothers also lacked proper understanding regarding ORS preparation, storage, and use. Some of the key barriers were the lack of proper knowledge, motivation, and compliance, along with misdirection from the elders and pharmacy drug sellers. Additional key facilitators to ORS use were trust towards doctors, positive attitude towards learning about ORS, community education, instructions written on the packet, and support from the healthcare providers. Conclusion A focused approach should be implemented to educate mothers on the correct preparation and administration of ORS for children, while also addressing and dispelling any misconceptions.